Efektivitas Programa Penyuluhan Pertanian Dan Kinerja Penyuluh Di Kabupaten Gunungkidul - Iswardayati, Nani Tri (Jurnal Ilmu-Ilmu Pertanian, 2015)
The title of research: Effectiveness of Agricultural Counselling Programs and Counselling Performance in Gunungkidul that held on February to December 2013. The purpose of this study was to: identify the realization of the planned counselling activity in agricultural counselling program, identify counselling activity that held by instructor (instructor performance), identify competencies of instructor and supporting factors of counselling activity, identify Effectiveness Of Agricultural counselling Programs, identify the influence of competences counselling and supporting factors the effectiveness of agricultural counselling program, identify the influences of the competences instructor and supporting factors counselling with instructor performance, identify impact of instructor performance and Effectiveness Of Agricultural counselling Programs. By using descriptive analysis obtained information: realization of counselling program average of 5.251 or lower category, the effectiveness of agricultural counselling program average of .436 or in medium category, instructor performance about 34, 211 or in a low category, the competence of instructor was at 54.923 or in medium category, and the supporting factors of counselling is about 176.269 or in the low category. There is influence of the competence instructor and the effectiveness of agricultural counselling program on the level of credibility(α) of 0.05 with significance 0.015, and there is influence between supporting factor and the effectiveness of agricultural counselling programs at the level of credibility (α) of 0.05 with significance 0.012. There isn't influences between instructor competence and the supporting factors of counselling with instructor performance in level of credibility (α) 0.05 with significance at 0.294 in instructor competence and 0.344 in supporting factors of counselling. Instructor performance was not affecting the effectiveness agriculture counselling program in level of credibility (α) 0.05 with significance 0.486.